The Impact of Different Winter Cover Crops on Weed Suppression and Corn Yield under Different Tillage Systems - Silin Liu; Zhiyi Ma; Ying Zhang; Zhongwen Chen; Xiao Du; Yinghui Mu (Agronomy, 2022)
White clover (Trifolium repens L.) and ryegrass (Lolium multiflorum L.) are widely used cover crops. This experiment investigated the potential of white clover (WC), ryegrass (RG), and fallow (FL) to inhibit the growth of weeds and the effect of their residue return to the field on subsequent crops in a cover crop-corn rotation system. Furthermore, we designed pot experiments to guide the scientific application of WC and RG. The results showed that the FL treatment had the highest mean weed biomass in two years (11.99 t ha−1) and the RG treatment recorded the lowest mean weed biomass in two years (2.04 t ha−1) as its early growth rate and aerial root cover. The combination of rotary tillage (RT) and WC recorded the highest total corn yield in two years (20.20 t ha−1) and an increase of 2.84% in the two-year average biomass of weeds compared to RT-FL. Compared to RT-FL, RT-RG treatments inhibited weed invasion by an average of 73%, but corn yield was reduced by 3.25%. Straw and soil ratios above 6:100 for RG resulted in stunted corn growth, including a reduction in fresh weight and chlorophyll content, and impaired photosynthesis, but this effect was not evident in WC treatment. From an ecological point of view, this study recommends RT-RG as a pre-crop for corn to reduce herbicide use.